Combined inhibition of FOSL-1 and YAP Using siRNA-lipoplexes reduces the growth of pancreatic tumor - Diego-González, Lara (2022)
Pancreatic cancer evades most of the current therapies and there is an urgent need for new treatments that could efficiently eliminate this aggressive tumor, such as the blocking of routes driving cell proliferation. In this work, we propose the use of small interfering RNA (siRNA) to inhibit the combined expression of FOSL-1 and YAP, two signaling proteins related with tumor cell proliferation and survival. To improve the efficacy of cell transfection, DODAB:MO (1:2) liposomes were used as siRNA nanocarriers, forming a complex denominated siRNA-lipoplexes. Liposomes and lipoplexes (carrying two siRNA for each targeted protein, or the combination of four siRNAs) were physico-chemically and biologically characterized. They showed very good biocompatibility and stability. The efficient targeting of FOSL-1 and YAP expression at both mRNA and protein levels was first proved in vitro using mouse pancreatic tumoral cell lines (KRASG12V and p53 knockout), followed by in vivo studies using subcutaneous allografts on mice. The peri-tumoral injection of lipoplexes lead to a significant decrease in the tumor growth in both Athymic Nude-Foxn1nu and C57BL/6 mice, mainly in those receiving the combination of four siRNAs, targeting both YAP and FOSL-1. These results open a new perspective to overcome the fast tumor progression in pancreatic cancer.